A review of the sustainable paddy-cattle integrated farming system: enhancing climate resilience and agricultural productivity - Hikmah, Aulia Nurul; Astaman, Putra; Hardianti, Hardianti; Zailan, Ahmad; Putri, Harmin Adijaya; Nurdin, Fadilah; Hakim, Muh. Haidir; Churriyah, A. Ni’mahtul; Raisa, Daeva Mubarika (Agriculture and Socio-Economic Journal, 2024)
Changes in temperature and extreme weather caused by the climate crisis have the potential to damage agricultural systems, threaten food security, and reduce agricultural productivity. This study aims to evaluate the integrated paddy-cattle farming system's resilience and capability to improve sustainability in the face of persistent difficulties. The research used a literature review approach with the aim of collecting, analyzing, and synthesizing previous research results relevant to the research topic. These sources will be drawn from reputable scientific databases, such as Google Scholar, Scopus, Web of Science, and JSTOR, which have peer-reviewed articles and journals. There has been no in-depth study of paddy-cattle resilience through literature review, which is the novelty of the article. The results of this review indicate that paddy-cattle integration systems can be an effective solution to the challenges of sustainable agriculture in the midst of climate change. However, to achieve sustainability, it requires supportive policies, training for farmers, and further research on the application of this system in various local conditions. This study provides insights for the development of more adaptive and sustainable farming systems, as well as optimizing synergies between crops and livestock in the face of climate change. This study has limitations in terms of the amount of literature that is not up-to-date and with a relatively small amount, therefore, future researchers related to the same topic should add more up-to-date and relevant literature citations.